2019
DOI: 10.23736/s0392-9590.19.04097-5
|View full text |Cite
|
Sign up to set email alerts
|

Early complications of endovenous laser ablation

Abstract: Background: The aim of this work was to evaluate the frequency, structure and characteristics of complications after endovenous laser ablation (EVLA). Methods: The study included 1247 consecutive patients (1417 limbs) with superficial venous insufficiency, treated with EVLA procedures with a wavelength of 1470 nm and automatic pull-back traction of the fiber. Control examinations using Duplex ultrasound were carried out on the second day after EVLA, and in 2 weeks and 1 month after the EVLA procedure. In certa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 16 publications
(4 reference statements)
1
4
0
2
Order By: Relevance
“…Otherwise, the incidence of thrombophlebitis after EVLA varies from 0-67% [11,12]. The most fearful complications such as deep vein thrombosis and consequent pulmonary embolism are rare-1,55% and 0,07%, respectively [13]. Another rare, but potentially life-threatening complication is suppurative thrombophlebitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Otherwise, the incidence of thrombophlebitis after EVLA varies from 0-67% [11,12]. The most fearful complications such as deep vein thrombosis and consequent pulmonary embolism are rare-1,55% and 0,07%, respectively [13]. Another rare, but potentially life-threatening complication is suppurative thrombophlebitis.…”
Section: Discussionmentioning
confidence: 99%
“…Another rare, but potentially life-threatening complication is suppurative thrombophlebitis. Usually, it is a condition that occurs in critically ill patients during and after intravenous injection or catheter insertion [13]. Otherwise, even with meticulous preparation in the operation eld, there is always the risk of infection with the introduction of a foreign body into the veins.…”
Section: Discussionmentioning
confidence: 99%
“…De forma geral, a pesquisa obteve proporções semelhantes a outras quanto aos efeitos adversos, inclusive não havendo efeitos colaterais graves e permanentes 11,19,20 . Especialmente em nossos dados, o fenômeno da dor pós-operatória teve certa relevância, estando, em alguns casos, associada a eritema local; no entanto, ela se resolveu dentro do período de 30 dias com o uso da analgesia não esteroidal.…”
Section: Discussionunclassified
“…Experimental data suggested that EVLA with a 1470-nm laser diode and radial fibers provides stable and valuable long-term outcomes in patients with either GSV or SSV insufficiency [ 150 ]. However, EVLA is not a unique surgical method of treatment, and the complication rate in patients was 4.87% of EVLA procedures [ 151 ]. An unintended complication of EVLA is endothermal heat-induced thrombosis of the common femoral vein.…”
Section: Research Progress and Applications Of Laser Technology In Intravascular Imaging And Treatmentmentioning
confidence: 99%
“…In EVLA, most complications can be avoided by developing a standard regulation on their detection and treatment as early as possible, such as deep vein thrombosis, pain syndrome, and fragmentation of the tip of the radial fiber [ 151 ]. Besides, ultrasound imaging has limitations for tracking the accurate location of the fiber tip inside small veins such as angular dependency and comet tail artifacts.…”
Section: Research Progress and Applications Of Laser Technology In Intravascular Imaging And Treatmentmentioning
confidence: 99%